An early case of neuromyelitis optica: on a forgotten report by Jacob Lockhart Clarke, FRS - Jarius, Sven; Wildemann, Brigitte (Multiple sclerosis journal, 2011)
We discuss a forgotten report by the famous British neuroanatomist, neuropathologist and neurologist Jacob Augustus Lockhart Clarke (1817-1880) about a 17-year-old girl with bilateral optic neuritis and longitudinally extensive transverse myelitis. This report, which appeared in 1865, i.e. 15 years prior to Wilhelm Erb’s much-cited paper on the coincidence of optic neuritis and acute myelitis, represents the first known account of a case of Devic’s syndrome or neuromyelitis optica in the English-language medical literature.
Gesehen am 04.07.2022